Synthesis and reactivity of an Ir(I) carbonyl complex bearing a carbazolide-bis(NHC) pincer ligand - Seyboldt, Alexander; Wucher, Barbara; Alles, Maria; Rominger, Frank; Maichle-Mössmer, Cäcilia; Kunz, Doris (Journal of organometallic chemistry, 2015)
Synthesis of the new iridium NHC pincer complexes [Ir(bimca)(CO)] (3a) and [Ir(bimcaEt)(CO)] (3b) is realized by salt metathesis of in situ generated [Li(bimca)] (2) with Ir(I) carbonyl precursors. In the case of Vaskas complex [IrCl(CO)(PPh3)2] we isolated the Ir(III) hydrido complex (4). Reactivity studies of Ir complex 3a towards allyl halides show the ready formation of η1 coordinated allyl ligands at the Ir(III) center in all cases.
Available online 8 November 2014
Gesehen am 16.06.2020